El camino de la inclusión de personas con necesidades educativas especiales en Costa Rica: aportes para la discusión - Richmond González, Viviana María (2009)
The present essay poses a series of reflections regarding the current state of Special Education, considering the well-made decisions along with the coexistent factors that weaken and annul the process towards an inclusive education. It examines the role of specific employees and their individual contributions, as well as the influence of the prevailing ideological system, special education, and the way in which projects related to this topic have been developed in Costa Rica. The objective is to contribute to this wideranging national discussion in order to understand more clearly what our common goals and strategies should be, in the interest of achieving a truly inclusive educational system.